2021
DOI: 10.1021/acsestengg.1c00258
|View full text |Cite
|
Sign up to set email alerts
|

Direct Potable Reuse: Are We Ready? A Review of Technological, Economic, and Environmental Considerations

Abstract: Meeting future water demand will require serious consideration of direct potable reuse (DPR) for many water agencies. There has been tremendous progress in the technologies needed to address the concerns that conventional and novel water contaminants pose. Yet, to date, only a few relatively small DPR operations have been installed. As we get closer to the point where regulations are finalized and serious investments are planned, there is a need to ask: Are we ready? In this Review, we explore the technologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 267 publications
0
13
0
Order By: Relevance
“…1,2 Many of these contaminants are recalcitrant and persistent, threatening the health of the ecosystem and human beings. 3 Advanced oxidation processes (AOPs) are treatment technologies that utilize reactive species (e.g., hydroxyl radicals (OH • ) and sulfate radical anions (SO 4…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Many of these contaminants are recalcitrant and persistent, threatening the health of the ecosystem and human beings. 3 Advanced oxidation processes (AOPs) are treatment technologies that utilize reactive species (e.g., hydroxyl radicals (OH • ) and sulfate radical anions (SO 4…”
Section: ■ Introductionmentioning
confidence: 99%
“…The increasing diversity and concentrations of organic contaminants in the environment have become a growing concern in past few decades. , Many of these contaminants are recalcitrant and persistent, threatening the health of the ecosystem and human beings . Advanced oxidation processes (AOPs) are treatment technologies that utilize reactive species (e.g., hydroxyl radicals (OH • ) and sulfate radical anions (SO 4 •– )) to break down organic contaminants in water. The redox potentials of OH • and SO 4 •– are in the ranges of +1.9 to 2.7 V NHE and +2.4 ( E 0 (SO 4 •– /SO 4 2– V NHE )), respectively, and can effectively oxidize many contaminants in water. The SO 4 •– -based AOPs have attracted greater attention in recent years because of its longer lifetime (30–40 μs) compared to that of OH • (<1 μs). , In addition, SO 4 •– can be applied over a wider pH range and is more selective and has lower reactivity than OH • toward interfering natural organic matter in water. , SO 4 •– are usually produced by activating peroxymonosulfate (PMS, HSO 5 – ) or peroxydisulfate (PDS, S 2 O 8 2– ) using ultraviolet or visible-light irradiation, carbonaceous materials, and transition metals. , Among metal activators, iron(II) in water (Fe(H 2 O) 6 2+ ) is attractive because it is environmentally friendly and a number of studies have already demonstrated its efficacy in activating PMS and PDS. It was also shown that the Fenton reaction always proceeds via inner-sphere complexation due to thermodynamic reasons. It is generally assumed that the reactive-oxidizing species in these systems are formed via the following reactions (reactions and ). Fe false( normalH 2 normalO false) 6 2 + + HSO 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, polyamide offers low resistance to fouling, defined by undesired adsorption and accumulation of feed components on the membrane surface or in the membrane pores. Membrane fouling can have a detrimental effect on membrane performance, substantially limiting water permeance/ membrane lifetime and necessitating chemical treatment for its reversal. Additionally, polyamide is sensitive to chlorine degradation. ,, This prevents the use of hypochlorite for biofouling management, necessitating complex staged treatment and/or alternative oxidizing agents. ,, While several groups have attempted to mitigate these issues through surface functionalization and/or by modifying the monomers used to form the polyamide selective layer, , the development of new polymer chemistries with inherent fouling and chlorine resistance would offer a simple and more sustainable solution. Membranes derived from polyelectrolyte multilayers (PEMs) represent one example of this ( e.g ., Pentair X-Flow HFW 1000 , ), although PEM membranes typically suffer the drawbacks of complex manufacturing and low stability in high ionic strength solutions …”
Section: Introductionmentioning
confidence: 99%
“…It is true that if the economic factor is ignored, we can achieve safe water reuse in accordance with any of the strictest water quality criteria. A number of successful cases of direct potable reuse have already provided strong evidence (Keller et al 2022).…”
Section: Introductionmentioning
confidence: 99%